Management of organizational culture in the conditions of enterprises digitalization - I. V. Groshev; A. V. Zheregelya; D. V. Shkolnyi (Управление)
Global digitalization processes are transcontinental and trans-industry in nature. There is no sphere vital activity, that does not feel the influence of digital institutions. Economic activity of agents is most sensitive to digital innovations and market shifts.The process of integrating digital innovations into the activities of large foreign companies, based on the study of foreign sources, has been considered. The dignities, advantages and disadvantages of this practice have been adduced. The consequences of the ill-conceived unbalanced policies of companies in the context of following fashion trends, happening in the digital environment, have been analyzed separately. The conclusion about the need to customize Russian companies to the modern requirements of the global digital market has been made. It is noted, that the domestic practice lags behind not so much in the mechanism of implementation of modern digital practices, but in the efficiency of their use and qualitative growth of the organizational structure due to the synergetic effect of digitalization of production and all related procedures and processes.The authors have concluded, that the management of a modern company should be based on the interaction of all stakeholders, and not due to the dominance of processes and hierarchy, which in turn, will require changes in the management of organizational culture. At the center of this interaction there are digital social tools, the useful functions of which are obvious, on the one hand, determining the dynamics of interaction (openness, sincerity, human communication), on the other - expanding the area of awareness of participants in the interaction. Herewith it has been noted, that the use of modern information products is necessary in a certain balance with standard offline work tools.